Patient-centered Outcomes in Participants of a Buprenorphine Monthly Depot (BUP-XR) Double-blind, Placebo-controlled, Multicenter, Phase 3 Study. Issue 6 (November 2019) - Ling, Walter; Nadipelli, Vijay R.; Solem, Caitlyn T.; Ronquest, Naoko A.; Yeh, Yu-Chen; Learned, Susan M.; Mehra, Vishaal; Heidbreder, Christian
Abstract : Objective: Opioid use disorder (OUD) is associated with physical, social, psychological, and economic burden. This analysis assessed the effects of RBP-6000, referred to as BUP-XR (extended-release buprenorphine), a subcutaneously injected, monthly buprenorphine treatment for OUD compared with placebo on patient-centered outcomes measuring meaningful life changes. Methods: Patient-centered outcomes were collected in a 24-week, phase 3, placebo-controlled study assessing the efficacy, safety, and tolerability of BUP-XR 300/300 mg (6 × 300 mg) and 300/100 mg (2 × 300 mg followed by 4 × 100 mg) injections in treatment-seeking participants with moderate-to-severe OUD. Measures included the EQ-5D-5L, SF-36v2, Medication Satisfaction Questionnaire, employment/insurance status, and healthcare resource utilization (HCRU). Changes from baseline to end of study were compared across treatment arms, using mixed models for repeated measures. Results: Participants receiving BUP-XR (n = 389) versus placebo (n = 98) had significantly greater changes from baseline on the EQ-5D-5L index (300/300 mg: difference = 0.0636, P = 0.003), EQ-5D-5L visual analog scale (300/300 mg: difference = 5.9, P = 0.017; 300/100 mg: difference = 7.7, P = 0.002), and SF-36v2 physical component summary score (300/300 mg: difference = 3.8, P < 0.001; 300/100 mg: difference = 3.2, P = 0.002). Satisfaction was significantly higher for participants receiving BUP-XR 300/300 mg (88%, P < 0.001) and 300/100 mg (88%, P < 0.001) than placebo (46%). Employment and percentage of insured participants increased by 10.8% and 4.1% with BUP-XR 300/300 mg and 10.0% and 4.7% with 300/100 mg but decreased by 12.6% and 8.4% with placebo. Participants receiving BUP-XR compared with placebo had significantly fewer hospital days per person-year observed. Conclusions: These results show the feasibility of measuring patient-centered life changes in substance use disorder clinical studies. Participants receiving up to 6 monthly injections of BUP-XR, compared with placebo, reported better health, increased medication satisfaction, increased employment, and decreased healthcare utilization. Abstract : Supplemental Digital Content is available in the text